An investigation on the drag reduction performance of bioinspired pipeline surfaces with transverse microgrooves - Liu, Weili; Ni, Hongjian; Wang, Peng; Zhou, Yi (Beilstein Journal of Nanotechnology, 2020)
A novel surface morphology for pipelines using transverse microgrooves was proposed in order to reduce the pressure loss of fluid transport. Numerical simulation and experimental research efforts were undertaken to evaluate the drag reduction performance of these bionic pipelines. It was found that the vortex ‘cushioning’ and ‘driving’ effects produced by the vortexes in the microgrooves were the main reason for obtaining a drag reduction effect. The shear stress of the microgrooved surface was reduced significantly owing to the decline of the velocity gradient. Altogether, bionic pipelines achieved drag reduction effects both in a pipeline and in a concentric annulus flow model. The primary and secondary order of effect on the drag reduction and optimal microgroove geometric parameters were obtained by an orthogonal analysis method. The comparative experiments were conducted in a water tunnel, and a maximum drag reduction rate of 3.21% could be achieved. The numerical simulation and experimental results were cross-checked and found to be consistent with each other, allowing to verify that the utilization of bionic theory to reduce the pressure loss of fluid transport is feasible. These results can provide theoretical guidance to save energy in pipeline transportations.
Keywords: bionic pipeline; drag reduction; drag reduction mechanism; fluid transport; transverse micro-grooves

(untitled) - Herring, H. (Energy, 2006)

(untitled) - Hasan, S. W.; Ghannam, M. T.; Esmail, N. (Fuel, 2010)

(untitled) - Ihle, C. F.; Tamburrino, A.; Montserrat, S. (Miner. Eng., 2014)

(untitled) - Chen, P.; Cheng, C.; Xin, J.; Wang, X.; Ye, D.; Feng, D. (Drilling of an Ultra-Deep Exploratory Well - Problems and Solutions: A Case Study, IADC/SPE Asia Pacific Drilling Technology Conference and Exhibition, Tianjin, China, 9.7.2012-11.7.2012)

(untitled) - Song, W.; Ni, H.; Wang, R.; Sun, B.; Shen, Z. (J. CO2 Util., 2017)

(untitled) - Meng, M.; Zamanipour, Z.; Miska, S.; Yu, M.; Ozbayoglu, E. M. (J. Pet. Sci. Eng., 2019)

(untitled) - Kamel, A.; Shah, S. N. (J. Pet. Sci. Eng., 2009)

(untitled) - Rodriguez Corredor, F. E.; Bizhani, M.; Kuru, E. (J. Fluids Eng., 2015)

(untitled) - Yang, S. Q.; Dou, G. (J. Fluid Mech., 2010)

(untitled) - Ceccio, S. L. (Annu. Rev. Fluid Mech., 2010)

(untitled) - Martell, M. B.; Rothstein, J. P.; Perot, J. B. (Phys. Fluids, 2010)

(untitled) - Gatti, D.; Cimarelli, A.; Hasegawa, Y.; Frohnapfel, B.; Quadrio, M. (J. Fluid Mech., 2018)

(untitled) - Feng, B.; Chen, D.; Wang, J.; Yang, X. (Adv. Mech. Eng. (London, U. K.), 2015)

(untitled) - Li, K.; Jing, D.; Hu, J.; Ding, X.; Yao, Z. (Beilstein J. Nanotechnol., 2017)

(untitled) - Schneider, J.; Djamiykov, V.; Greiner, C. (Beilstein J. Nanotechnol., 2018)

(untitled) - Li, D.; Guo, Z. (Appl. Surf. Sci., 2018)

(untitled) - Florian Baron, C.; Mimidis, A.; Puerto, D.; Skoulas, E.; Stratakis, E.; Solis, J.; Siegel, J. (Beilstein J. Nanotechnol., 2018)

(untitled) - Wen, L.; Weaver, J. C.; Lauder, G. V. (J. Exp. Biol., 2014)

(untitled) - Bixler, G. D.; Bhushan, B. (J. Colloid Interface Sci., 2013)

(untitled) - Etsion, I.; Kligerman, Y.; Halperin, G. (Tribol. Trans., 1999)

(untitled) - Ibatan, T.; Uddin, M. S.; Chowdhury, M. A. K. (Surf. Coat. Technol., 2015)

(untitled) - Bixler, G. D.; Bhushan, B. (Adv. Funct. Mater., 2013)

(untitled) - Liu, H.; Yang, Q. H.; Pei, X.; Zheng, L. C.; Fu, T.; Shi, B. R. (Acta Petrol. Sin., 2016)

(untitled) - Meng, M.; Zamanipour, Z.; Miska, S.; Yu, M.; Ozbayoglu, E. M. (Rock Mech. Rock Eng., 2019)

(untitled) - Walsh, M. J. (AIAA J., 1983)

(untitled) - Viswanath, P. R. (Prog. Aerosp. Sci., 2002)

(untitled) - Dean, B.; Bhushan, B. (Philos. Trans. R. Soc., A, 2010)

(untitled) - Rastegari, A.; Akhavan, R. (J. Fluid Mech., 2018)

(untitled) - Bechert, D. W.; Bruse, M.; Hage, W. (Exp. Fluids, 2000)

(untitled) - Zhang, D.-y.; Luo, Y.-h.; Li, X.; Chen, H.-w. (J. Hydrodyn., 2011)

(untitled) - Dean, B.; Bhushan, B. (Appl. Surf. Sci., 2012)

(untitled) - Dai, W.; Alkahtani, M.; Hemmer, P. R.; Liang, H. (Friction, 2019)

Proceedings of the Progress in astronautics and aeronautics - Walsh, M. J. (Drag characteristics of V-groove and transverse curvature riblets, 1980)

(untitled) - Tokunaga, H. (LES of channel flow with transverse riblet and drag reduction, 37th Aerospace Sciences Meeting and Exhibit, Reno, NV, USA, 11.1.1999-14.1.1999, 1999)

(untitled) - Dou, Z.; Wang, J.; Chen, D. (J. Bionic Eng., 2012)

(untitled) - Mariotti, A.; Buresti, G.; Gaggini, G.; Salvetti, M. V. (J. Fluid Mech., 2017)

Direct and large eddy simulation of turbulent flow in a cylindrical pipe geometry - Eggles, J. G. M. (Delft University of Technology, 1994)

(untitled) - Rahman, A.; Corredor, F. E. R.; Bizhani, M. (Near Wall Turbulence Characteristics of a Drag Reducing Polymer Fluid Flow in Concentric Annulus Using CFD, ASME 2013 International Mechanical Engineering Congress and Exposition, San Diego, California, USA, 15.11.2013-21.11.2013)

Engineering fluid mechanics - Yamaguchi, H. (Springer, 2008)

(untitled) - Chung, S. Y.; Rhee, G. H.; Sung, H. J. (Int. J. Heat Fluid Flow, 2002)

(untitled) - Jung, Y. C.; Bhushan, B. (J. Phys.: Condens. Matter, 2010)